Long Bone Mineral Loss, Bone Microstructural Changes and Oxidative Stress After Eimeria Challenge in Broilers - Tompkins, Y. H.; Teng, P.; Pazdro, R.; Kim, W. K. (Frontiers in Physiology, 2022)
The objective of this study was to evaluate the impact of coccidiosis on bone quality and antioxidant status in the liver and bone marrow of broiler chickens. A total of 360 13-day old male broilers (Cobb 500) were randomly assigned to different groups (negative control, low, medium-low, medium-high, and highest dose groups) and orally gavaged with different concentrations of Eimeria oocysts solution. Broiler tibia and tibia bone marrow were collected at 6 days post-infection (6 dpi) for bone 3-D structural analyses and the gene expression related to osteogenesis, oxidative stress, and adipogenesis using micro-computed tomography (micro-CT) and real-time qPCR analysis, respectively. Metaphyseal bone mineral density and content were reduced in response to the increase of Eimeria challenge dose, and poor trabecular bone traits were observed in the high inoculation group. However, there were no significant structural changes in metaphyseal cortical bone. Medium-high Eimeria challenge dose significantly increased level of peroxisome proliferator-activated receptor gamma (PPARG, p < 0.05) and decreased levels of bone gamma-carboxyglutamate protein coding gene (BGLAP, p < 0.05) and fatty acid synthase coding gene (FASN, p < 0.05) in bone marrow. An increased mRNA level of superoxide dismutase type 1 (SOD1, p < 0.05) and heme oxygenase 1 (HMOX1, p < 0.05), and increased enzyme activity of superoxide dismutase (SOD, p < 0.05) were found in bone marrow of Eimeria challenged groups compared with that of non-infected control. Similarly, enzyme activity of SOD and the mRNA level of SOD1, HMOX1 and aflatoxin aldehyde reductase (AKE7A2) were increased in the liver of infected broilers (p < 0.05), whereas glutathione (GSH) content was lower in the medium-high challenge group (p < 0.05) compared with non-challenged control. Moreover, the mRNA expression of catalase (CAT) and nuclear factor kappa B1 (NFKB1) showed dose-depend response in the liver, where expression of CAT and NFKB1 was upregulated in the low challenge group but decreased with the higher Eimeria challenge dosage (p < 0.05). In conclusion, high challenge dose of Eimeria infection negatively affected the long bone development. The structural changes of tibia and decreased mineral content were mainly located at the trabecular bone of metaphyseal area. The change of redox and impaired antioxidant status following the Eimeria infection were observed in the liver and bone marrow of broilers.